2014
DOI: 10.3892/or.2014.3363
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lifeguard β-isoform in the development of breast cancer

Abstract: In the last century there has been great progress in the treatment of breast cancer by improving drug and radiation therapy as well as surgical techniques. Despite this development, breast cancer remains a major cause of death among women in Europe and the US. The cause of breast cancer at the cellular level is still not fully understood. In the present study, we investigated the expression of the Lifeguard β-isoform in breast cancer tissues. In contrast to Lifeguard, the β-isoform has one transmembrane domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…This isoform maintains the anti‐apoptotic potential and was found to be strongly expressed in breast cancer tissues (Dastagir et al . ).…”
Section: Faim2mentioning
confidence: 97%
See 1 more Smart Citation
“…This isoform maintains the anti‐apoptotic potential and was found to be strongly expressed in breast cancer tissues (Dastagir et al . ).…”
Section: Faim2mentioning
confidence: 97%
“…Recent studies described a new isoform of FAIM2, named FAIM2b, which lacks one of the transmembrane domains. This isoform maintains the antiapoptotic potential and was found to be strongly expressed in breast cancer tissues (Dastagir et al 2014).…”
Section: Faim2mentioning
confidence: 99%
“…It is possible that a part separated from the protein complex. In a study of Dastagir et al ( 15 ) in 2014 another form of LFG was examined, the β-isoform. This is a shorter form of Lifeguard and is also expressed in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…This is a shorter form of Lifeguard and is also expressed in breast cancer cell lines. The study even showed that the smaller isoform of the Lifeguard enacts in an equally important role in the development of breast cancer as LFG itself ( 15 ). Hence, the band at the size of 60 kDa possibly indicates a bond between TRIM21 and β isoform of Lifeguard.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, primary breast cancer cell lines and tumor tissues showed a stronger expression of the isoform compared with established cell lines, in which the longer isoform was strongly expressed. The isoform of the protein may also protect cells of the mammary gland from apoptosis and result in an increase in gene expression of members of the Akt signaling pathway ( 9 ).…”
Section: Introductionmentioning
confidence: 99%